Influence of pasteurization on the color of Citrus microcarpa mathematical models - Mabanta, Anais Carla D. (University of the Philippines Diliman, 2007)
ABSTRACT This study was conducted to establish mathematical models in order to describe the influences of pasteurization time and temperature combinations on the color characteristics of Citrus microcarpa juice. Using a Central Composite Rotatable Design, the thermal process effects were determined through a response surface model. To describe these, the L*, a*, and b* values of the treated juices were fitted into second-order models. The individual and interactive parameters were significant (p<0.05) for L* of the calamansi juice. The quadratic effect temperature was not significantly associated with a* of the calamansi juice. The interactive effects of time and temperature were also not significant with both a* and b* values of the calamansi juice while all the other parameters were found to be significantly associated to a* and b*.